The Family Right from the Background of the Fichtean Natural Right - Arrese Igor, Hector Oscar (2016)
The Fichtean theory of self-consciousness and recognition, published in 1796 and 1797, must be understood in terms of the mutual formation of subjects insofar as they are rational and free beings. It is for this reason that this paper criticizes Stephen Darwall's interpretation from the second persońs perspective. It also reconstructs the Fichtean theory of family, suggesting evidence of the relationships of recognition that structure it. In this way there are analogies between the original situation of summons and the formative relationships at the core of the family community.